2012
DOI: 10.1177/0971890720120203
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Capital Structure Determinants of Public Sector and Private Sector Companies in India

Abstract: The paper attempts to identify factors which are essential while making capital structure decisions for public sector companies and private sector companies in India. It studies the impact of ten independent variables on three dependent variables for each of the sectors respectively. Most of the researches in determinants of capital structures till date have been done in developed economies, with limited research in emerging markets. This research will add to the understanding of this issue in emerging market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…According to agency theory, a firm’s ability to service its debt reduces agency costs and motivates a higher use of debt to enjoy higher tax shield. Studies such as Eriotis et al (2007), Lima (2010), Handoo and Sharma (2012), Banerjee and De (2014) have used debt service capacity ratio as an independent variable to determine its impact on capital structure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to agency theory, a firm’s ability to service its debt reduces agency costs and motivates a higher use of debt to enjoy higher tax shield. Studies such as Eriotis et al (2007), Lima (2010), Handoo and Sharma (2012), Banerjee and De (2014) have used debt service capacity ratio as an independent variable to determine its impact on capital structure.…”
Section: Methodsmentioning
confidence: 99%
“…The empirical result of the studied Nigerian firms suggest that interest costs borne by debt are counterbalanced by the tax benefits availed. Handoo and Sharma (2012) have done a comparative study of capital structures of Indian state-owned and privately held companies. They found that for the state-owned (public) companies, both equity and debt funding options are available; however, when raising debt funding, factors like firm size, age of the firm, cost of capital and debt servicing capability tend to play a significant role.…”
Section: Literature Reviewmentioning
confidence: 99%